Translation and validation of the survey employee perception to assess lean implementation tool to brazilian portuguese - Sarantopoulos, Alice; Min, Li Li; Calado, Robisom Damasceno [UNESP]; Componation, Paul J. (Elsevier, 2013)
The Employee Perception to assess Lean Implementation Tool (EPLIT) is an efficient measure of an organizations Lean implementation using employee perception. The objective was to translate, adapt and validate the questionnaire content into a Brazilian Portuguese version. The translation and adaptation into Brazilian Portuguese was carried out in five steps: translation, synthesis, back translation, committee evaluation and the application of questionnaire (pre-test).The translated and adapted 29-item Portuguese version of the scale and instructions produced an instrument called Percepcao do Funcionário para avaliar a Ferramenta de Implementacao do Lean. In the assessment by the target population, 30 employees, being 10 from companies with lean production and 20 from companies that do not have lean, from different companies, answered the questionnaire and showed good understanding of the instrument (average=4.7) in the five scores scale. The questionnaire proved to be easily comprehensible. The questionnaire can contribute in some way to assess the implementation of Lean in a company according to the view of the employees. One suggestion would be to modify EPLIT to cater to the healthcare. © IFAC.